The effect of the four-pillar strategy on the performance of the transmission and preparation skills in volleyball - juda, sawsan; Al-Zuhairi, Najla (Journal of Physical Education, 2025)
The aim of the research is to prepare practical volleyball lessons by using the four pillars strategy for middle school students, and to identify the effect of the four pillars strategy in performing the transmission and volleyball skills in the second intermediate students, to assume that the two researchers assume that there are no statistically significant differences between the results of my skill performance tests Sending and preparing tribal and remote volleyball for the experimental and controlled groups, and there are no statistically significant differences between the results of the performance of the transmission and preparation skills of the volleyball between the two experimental and control groups, and the research community available in the second -grade middle -grade students persistently in the morning study in the high school for boys within the secondary school within Forms of the General Directorate for Baghdad Education/ Rusafa for the academic year (2023/2024), The total number of (180) students, who are inherently distributed to the six study people, the application sample of the number of (40) random students in the two divisions (A) and (C) represented (22,222 %) of the origin society, and after preparing the performance tests The skill and preparation of practical lessons in this strategy was applied after tribal tests by experimenting with a period of (8) weeks at a rate of (1) one lesson per week and for each skill (4) consecutive weeks, and then conducting dimensional tests and processing the results automatically with a system (SPSS) so that the conclusions and recommendations are to apply The strategy of the four pillars in practical physical education is suitable for middle school students, and helps in improving the performance of the transmission and preparation skills of their volleyball, and they outperform the improvement level of the performance of these two skills for students who study without them, and it is necessary to increase interest in modernizing teaching strategies in active learning and employ their applications In the lesson of physical education by adopting individual differences to suit the age and level of middle school students, It is necessary to include the applications of the strategy of the four pillars in the preparation courses and training in the General Directorates of Training and to introduce teachers to how to employ them in practical lessons of volleyball because of their positive returns to the skill factor for second-grade intermediate students.